14 A quality improvement collaborative to improve maternal complication identification and use of C-section and blood transfusion in bihar, india. (25th November 2019) - Jackson, Clark; Mehndiratta, Abha; Parry, Gareth; Shah, Hemant; Mahapatra, Tanmay; Moharana, Prabir; Barker, Pierre; Ali, Azhar
Abstract : Background: Bihar, India has higher maternal mortality rates than the country on average. A Collaborative Quality Improvement (CQI) program was created to improve data transparency and accuracy, with the aim of increasing maternal complication identification and improving key life-saving processes for cesarean section and blood transfusion. Objectives: To estimate the impact of the CQI program on identification of maternal complications and use of C-section and blood transfusion for maternal complications in participating hospitals relative to non-participating facilities in Bihar. Methods: Ten district hospitals participated in the collaborative from February 2018 to September 2019. Activities included leadership and improvement workshops; learning sessions; and monthly onsite support provided by IHI and CARE India. Data from HMIS was used to assess change from baseline to after the start of the collaborative in CQI district hospitals, compared to non-participating district hospitals for: maternal complication identification, C-sections, and blood transfusions. Results: Figures 1–3 illustrate improvement over time for all measures. For example, across all CQI hospitals, control chart methodology suggested C-sections (percent all births) increased from a rate of 6.2% (95% CI 5.9%, 6.7%) at baseline to 8.3% (95% CI 7.8%, 9.0%) after the start of the collaborative. Comparative analysis found C -sections increased by 2.2% (95% CI 1.8%, 2.64%) per month in CQI facilities during the collaborative period, relative to non-CQI facilities. Conclusions: Application of this QI collaborative led to improvement in identification of maternal complications and use of C-section and blood transfusion.